In/audible and in/visible: Reflections on university-level teacher training from the viewpoint of critical theory on racism and pros-pects for the acknowledgment and recognition of diverse perspectives - Kasatschenko, Tatjana; Zitzelsberger, Olga (Momentum Quarterly, 2020)
The following article outlines an educational project of critical inquiry into racism to sensitize pre-service teachers and the teaching staff at a higher education institution and the associated theoretical and preliminary considerations. The participatory project structure is preceded by questions focusing on the in/audibility and in/visibility of diverse and often marginalized social positions. First experiences with regard to the opportunities as well as challenges provide insights into the first year of the project in the field of educational professionalization on several levels.